Legal Protection for Consumers Against Buying and Selling Goods Transactions Through Online Shops - Aditya Migi Prematura (Faculty of Law, Universitas Pekalongan, 2021)
The development of technology in the era of industrial revolution 4.0 is very rapid. These developments triggered developments in all sectors, one of the most affected by the industrial revolution 4.0 was the trade sector. In the current era of 4.0, trade has begun to develop from conventional trading that is trading through physical markets or more often we are familiar with supermarkets, malls, mini markets, and so forth to trade through online markets or more commonly known as E-Commerce. This is a fresh wind for consumers because with the switch of trade through E-commerce, a myriad of conveniences offered by the E-commerce. The conveniences include that consumer do not need to leave the house to buy an item, or in other words a trade transaction can be done anywhere without having to spend special time to travel to a store or shopping center. Not only positive things and conveniences caused by this development, but a myriad of problems that nowadays often occur in online buying and selling activities. Starting from goods that do not match the description or information provided by businesses to the delay of goods that have been promised by businesses, to other problems that essentially harm the consumer.